Understanding Clothing Selection: The Perfect Ways of Choosing Men’s Suit Jacket for Good Grooming - Opoku, Moses; Sarah, Baiden; Bakker-Edoh, Dymphna (Integrated Journal for Research in Arts and Humanities, 2023)
Suit jacket as an outer garment has been able to maintain its exclusivity, dignity and constructional processes over the years. Its production appears very interesting and challenging. Apparently, selecting the right suit jacket for good grooming sometimes seems difficult and, if care is not taken, one may end up opting for wrong size. In some occasions, the choice of lapel type in conformity with an individual’s figure type may create some kind of pandemonium. The study seeks to bring to limelight major issues involving the selection of perfect suit jacket. The specific objectives were to identify the materials for making suit, examine the factors that contribute to perfect suit production and identify some common problems associated with suit construction and selection. The qualitative research design was employed to conduct an in-depth analysis of the core components of a well-tailored suit jacket. Research instruments such as observation and photography were used for the required data of the study. The findings revealed that choosing the perfect suit for good grooming can be challenging since the embodiment of suit jacket involves several technical issues. Again, the vital parts of suit jacket such collar, lapel, shoulders, sleeve and body measurements equally contribute to good fit.